The Routledge Handbook of Transport Economics - Cowie, Jonathan; Ison, Stephen (London : Taylor and Francis, 2017)
"The Routledge Handbook of Transport Economics offers the first state of the art overview of the discipline of transport economics as it stands today, reflective of key research and policy. Transport is an important area of study and one which is problem rich, stimulating a great deal of debate in areas which impact on everyday lives. Much of this focuses on the practicalities of the modern-day phenomenon of mass movement and all of the issues which surround it. The discipline of economics is central to this debate, and consequently the study and application of transport economics has a chief role to play in seeking to address subjects relating to major transport issues. It can be argued that at the very heart of any transport issue or problem lies the underlying economics of the situation & understand that and you alleviate the problem.? Featuring contributions from world-leading scholars and practitioners from across the globe, all of the chapters within this book are written from a practical perspective; theory is applied and developed using real-world examples. The book examines concepts, issues, ideas and practicalities of transport provision in five key topic areas:public transportpublic transport reformeconomic development and transport modellingtransport and the environmentfreight transport.A real strength of the book is in linking theory to practice, and hence the 'economics' that are examined in this text are not the economics of the abstract, but rather the economics of everyday living. Practical and insightful, this volume is an essential reference for any student or researcher working in all areas of transport provision, ranging from planning, appraisal, regulation and freight; and for all practitioners looking to develop their professional knowledge and who are seeking professional accreditation."--Provided by publisher.
chapter 1 Introduction / Jonathan Cowie -- part I Public transport -- chapter 2 Passenger rail structure and reform / Simon Blainey -- chapter 3 Bus economics / Peter White -- chapter 4 The pricing of public transport services / Corinne Mulley -- chapter 5 Perfect information and intelligent transport systems / John D. Nelson -- chapter 6 Passenger air traffic / Peter Forsyth -- part II Public transport reform -- chapter 7 Public service contracts -- The economics of reform with special reference to the bus sector / David A. Hensher -- chapter 8 Rail regulation / Chris Nash -- chapter 9 The impact of regulatory reform on public transport markets / John Preston -- chapter 10 Airline deregulation / Lucy Budd -- part III Forecasting, public choice and transport modelling -- chapter 11 Forecasting the demand for transport / John Bates -- chapter 12 The principles behind transport appraisal / John Nellthorp -- chapter 13 Congestion pricing / Jonas Eliasson -- chapter 14 Transport modelling and economic theory / Kathryn Stewart -- chapter 15 Efficiency assessment in transport service provision / Rico Merkert -- part IV Transport and the environment -- chapter 16 The environment in the provision of transport / Maria Attard -- chapter 17 The tools available under a green transport policy / Tom Rye -- chapter 18 Options and practicalities of a green transport policy / Rebecca Johnson -- chapter 19 Sustainable travel or sustaining growth? / Robin Hickman -- part V Freight transport -- chapter 20 Short sea shipping and ferries / James D. Frost -- chapter 21 Competition and complementarity in road freight -- Key drivers and consequences of a dominant market position / Jonathan Cowie -- chapter 22 Rail freight / Allan Woodburn -- chapter 23 Air cargo / Thomas Budd -- chapter 24 Intermodal freight transport / Jason Monios.
Keywords: Transportation; Business logistics; Industrial organization (Economic theory).; International economic relations; Aerospace & Air Transport Industries; Industrial Economics; International Economics; Railway Transport Industries; Road Transport Industries; Shipping Industries; Supply Chain Management; Transport Industries; TRANSPORTATION / Automotive / General; TRANSPORTATION / General